Equity before 'Equity'. - Humphreys, Stephen (Modern Law Review, 2023)
The notion of 'equity' is undergoing conceptual repositioning in international law today, embracing individuals as well as states and gaining an association with human rights and the politics of protest. In the context of these developments, the present paper enquires into the premodern roots of this ancient and rich term through three historical vignettes: first, the emergence of aequitas in Roman law – as a source of law anchored in analogy and empathy – and in particular its relevance to the ambiguous status of slaves; second, the importance of 'natural equity' to the consolidation of 'natural rights' during the Franciscan poverty debate in 14th century Europe, and finally, 'common equity' in the rights‐based constitutional order proposed by the Levellers in 1640s England. In its root sense, I conclude, what we might call 'radical equity' has historically lent itself to trenchant critique of the law, centred on the individual as subject of right.